Experience of a single institution treating foramen magnum meningiomas - (:unkn) unknown (ELSEVIER SCI LTD, 2004)
Despite the introduction of skull base approaches, there is still controversy in the optimum surgical management of foramen magnum meningiomas. Between January 1990 and January 2003, 22 patients underwent 23 surgical procedures with a diagnosis of foramen magnum meningioma at Marmara University, Department of Neurosurgery. The suboccipital approach was used for 2 posteriorly located tumors with radiological total removal. The paramedian suboccipital approach was replaced by the far-lateral modification in the treatment of ventral meningiomas. 1 of the 20 ventral tumors was operated twice. The classical suboccipital approach was followed by the far-lateral modification. A gross-total removal was achieved in 21 patients. The overall morbidity was 32%. No specific and clinically significant complications attributable to the far-lateral modification were observed. The far-lateral approach has improved the success of surgery in ventrally located lesions. The posterior suboccipital approach is still indicated in the removal of lesions placed posterior to the clentate ligament. (C) 2004 Elsevier Ltd. All rights reserved.
Keywords: foramen magnum; meningioma; far-lateral approach; skull base surgery; LATERAL TRANSCONDYLAR APPROACH; SUBOCCIPITAL APPROACH; CERVICAL-SPINE; BENIGN-TUMORS; RADIOSURGERY; CORD